Projekt Etymologického slovníku české a slovenské vinohradnické a vinařské terminologie - Villnow Komárková, Jana (Slavia Centralis, 2020)
This paper presents the research project The language of traditional viticulture and viniculture in the Central European area: etymology and areal linguistics as well as its main result – the electronic Etymological dictionary of the Czech and Slovak viticultural and vinicultural terminology. This is a small-scale dictionary, in which the collected Czech (and comparatively also Slovak) terms are etymologized and their development is described. The analysis of the Czech and Slovak words is implemented in a broader geographic context – the so-called Central European wine-growing area. The equivalent terminological systems of the neighbouring languages are researched – the German (respectively Austrian), Hungarian, Slovenian, Croatian and Polish.